Unilateral hamstring foam rolling does not impair strength but the rate of force development of the contralateral muscle - Ye,Xin; Killen,Benjamin S.; Zelizney,Krista L.; Miller,William M.; Jeon,Sunggun (PeerJ, 2019)
Background Self-administered foam rolling (SAFR) is an effective massage technique often used in sport and rehabilitation settings to improve range of motion (ROM) without impairing the strength performance. However, the effects of unilateral SAFR on contralateral non-intervened muscle’s rate of force development (RFD) are unknown. Therefore, the purpose of this investigation was to examine the acute effects of unilateral hamstrings SAFR on the contralateral limb flexibility, the isometric strength, and the RFD parameters. Methods Thirty-four subjects (21 women) completed two separate randomly sequenced experimental visits, during which the control (rested for 10 min) or ten, 30-second SAFR were performed with the dominant hamstring muscle group. Before (Pre) and after (Post) the interventions, the contralateral hip flexion passive ROM, the maximal explosive isometric strength of the contralateral knee flexors with the corresponding prime mover muscles’ surface electromyographic (EMG) amplitude were measured. Separate two-way (time ×intervention) repeated measures analyses of variance (ANOVAs) were used to examine the potential changes of the dependent variables. Results The SAFR significantly improved the contralateral limb ROM (Pre vs. Post: 68.3 ± 21.0 vs. 73.2 ± 23.2 degrees, p < 0.001; d = 0.22). No change was found for the contralateral isometric strength or the maximal EMG amplitude. For the RFD parameters, the percent changes of the RFDs for the first 50, 100, and 200 ms of the maximal explosive isometric contraction were −31.2%, −16.8%, and −10.1%, respectively, following the unilateral SAFR, relative to the control condition. In addition, the decrement of the first 50-ms RFD reached statistical significance (p = 0.007; Cohen’s d = 0.44). Conclusion Ten sets of 30-second unilateral hamstring SAFR improved the ROM of the non-intervened contralateral limb, but decreased its ability to generate force, especially during the early phase (e.g., 50 ms) of the maximal explosive contraction.
Keywords: Crossover; Isometric strength; Surface Electromyography; Explosive Force; Flexibility